Improved voice over Internet protocol for wireless devices - Roslin, Raihan Jannati; Khalifa, Othman Omran; Bhuiyan, Sharif Shah Newaj (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Voice over Internet Protocol (VoIP) becomes an attractive communications option for consumers specially for current young generations where facebook, whatsApp and other communicationssocial media in use. VoIP allows us to make telephone calls over the Internet and include signaling, controlling and transport mechanisms. However, the speech quality is impairedby packet losses, which are common on wireless links, and by high transmission delays. The aimof this paper is to present a method to improve the speech quality for voice-over-internet protocol (VoIP). Since the performance of unreliable voice transmission (Voice over IP) over wireless links is measured not by the throughput but by the perceptual speech quality. In this scheme there three main elements of VoIP are signaling protocol, audio codec and transport layer play a big role in providing the best VoIP speech quality. The quality of speech is determinedusing the Mean Opinion Score (MOS) after the values of jitter and end-to-end delay has been measured. Thus, the best couple of audio codec and signaling protocol through the quality ofthe speech quality produced.